How monetary policy works - Mahadeva, Lavan; Sinclair, Peter (London ; New York : Routledge, 2005)
This book , a collaboration between practitioners of monetary policy across the world, helps to provide a foundation for understanding monetary policy works in all its complex glory. Using models, case studies and new empirical evidence, the contributors to this book help readers on many levels develop their technical expertise.
Published in association with the Bank of England
Includes bibliographical references (p. [411]-438) and index.
gau 10/06/14, nmn 16/07/14
Loans
Keywords: Monetary policy